IMPORTANCE OF DIGITAL EDUCATIONAL TECHNOLOGIES IN TEACHING FOREIGN LANGUAGES (American Journal of Pedagogical and Educational Research, 2023)
This comprehensive exploration delves into the pivotal role of digital educational technologies in the realm of teaching foreign languages. Unveiling a transformative landscape, the article navigates through the multifaceted impacts of technology on language acquisition, from personalized learning journeys and accessible language resources to real-time collaboration and the cultivation of digital literacy skills. The narrative unfolds as a nuanced exploration of how digital tools enhance engagement, foster accessibility, and propel language education into a dynamic era of continuous evolution and innovation.